Finite element modeling of viscoelastic core sandwich panels - R. A. Moreira (2004)
Thin layers of viscoelastic materials are often used in the core of sandwich plates or in surface constrained damping treatments as an effective way to reduce dynamic response of light structures. However the usual approach to model these structures, using a layered scheme of plate and brick finite elements, demands a cumbersome spatial modelling task. In this work a layerwise-based facet-shell finite element model is proposed which is able to describe accurately the stiffness, damping and mass of the composite plate. Some fi- nite element remedies are applied in the finite element formulation in order to improve its membrane formulation, avoid shear locking and introduce the drilling degrees of freedom. Experimental results obtained on several sandwich plates with viscoelastic layers are used to validate the applicability of the proposed model for the simulation of sandwich plates with a single or multiple viscoelastic cores.